2001
DOI: 10.1080/107175401316906874
|View full text |Cite
|
Sign up to set email alerts
|

Transport Functions of Riboflavin Carriers in the Rat Small Intestine and Colon: Site Difference and Effects of Tricyclic-Type Drugs

Abstract: The present study was aimed at kinetically characterizing the newly found carrier-mediated riboflavin transport system in the rat colon, comparing it with that in the small intestine, and also probing the potential roles of these transport systems in intestinal drug absorption. Riboflavin transport, evaluated by measuring the initial uptake into everted intestinal tissue sacs, was saturable with a Michaelis constant (Km) of 0.13 microM and a maximum transport rate (Jmax) of 0.74 pmol/min/100 mg wet tissue weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…Not only RF transport in the small intestine (site of absorption of dietary RF) is inhibited by chronic exposure to ethanol, but also transport of the vitamin in the colon (the site of absorption of the bacterially synthesized RF) (12,34,39) is (Table 1) and normalized relative to rat ␤-actin. Data are means Ϯ SE of 4 separate samples from 4 rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only RF transport in the small intestine (site of absorption of dietary RF) is inhibited by chronic exposure to ethanol, but also transport of the vitamin in the colon (the site of absorption of the bacterially synthesized RF) (12,34,39) is (Table 1) and normalized relative to rat ␤-actin. Data are means Ϯ SE of 4 separate samples from 4 rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the normal microflora of the large intestine synthesizes RF (11,31) and that mammalian colonocytes have an efficient carrier-mediated mechanism for RF uptake via RF transporter (39). Therefore, we examined the effect of chronic alcohol feeding on the initial rate of carriermediated RF (24 nM) uptake by rat colon using colonic sheets.…”
Section: Effect On Rf Uptake In Rat Colon (Large Intestine)mentioning
confidence: 99%
“…8,23 Other causes of riboflavin deficiency include hypothyroidism, borate ingestion, phototherapy, and treatment with chlorpromazine, probenicid, and tricyclic antidepressants. 8,24 Phototherapy, similar to light exposure, results in degradation of riboflavin. Borate induces deficiency through displacement from its binding sites, increased urine losses, and inhibition of riboflavin-containing enzymes.…”
Section: Riboflavin (Vitamin B 2 )mentioning
confidence: 99%
“…Values represent computer-fitted parameters: J max , maximum uptake rate; K m , Michaelis constant; a) data from Yuasa et al 6) ; b) Tomei et al 2) cholate transport in the colon was also found to be Na ϩ -dependent in our preceding study, 3) the trace level of ASBT might be functionally modulated in the colon in a different manner to that in the small intestine, or an unidentified ASBT isoform or some other class of carrier might be responsible for taurocholate transport in the colon, like the above speculation about the D-glucose carrier.…”
Section: 7mentioning
confidence: 99%